2011
DOI: 10.3109/0142159x.2011.611402
|View full text |Cite
|
Sign up to set email alerts
|

Engagement and opportunity in clinical learning: Findings from a case study in primary care

Abstract: These findings support and develop existing literature on learning in other clinical settings. They are consistent with socio-cultural theories of learning, but develop this literature within the context of clinical education. Engagement and learning occurred in transient learners in the absence of prolonged participation, belonging or a clear trajectory of learning. The study offers evidence from multiple learner perspectives as to how the learning environment might be enhanced in all educational settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 22 publications
1
37
0
Order By: Relevance
“…The students' reflections suggest this was successful. Our findings are in keeping with previous research about the LE (Hutchinson 2003;Kendall et al 2005;Pearson and Lucas 2011). What our research adds are key features of a safe LE which students identified that can be deliberately incorporated into a LE.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The students' reflections suggest this was successful. Our findings are in keeping with previous research about the LE (Hutchinson 2003;Kendall et al 2005;Pearson and Lucas 2011). What our research adds are key features of a safe LE which students identified that can be deliberately incorporated into a LE.…”
Section: Discussionsupporting
confidence: 89%
“…Given the constraints of the clinical workplace, research into the contexts, volume and timing of observation and feedback is needed. Simulations are a useful step towards work-based learning and clinical practice because it is easier to control the LE for variables such as feedback and support (Dornan et al 2007;Pearson and Lucas 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement in learning appears to be developed through four essential elements: recognition, respect, relevance, and emotion. Clinical Opportunities include the availability of patient encounters [1]. It is well documented that medical students receive their best training when this is done in PHCCS, due to many factors such as small group sessions [1, 2] and the presence of real patients for hands-on training which includes the development of effective patient interactions along with understanding chronic diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical Opportunities include the availability of patient encounters [1]. It is well documented that medical students receive their best training when this is done in PHCCS, due to many factors such as small group sessions [1, 2] and the presence of real patients for hands-on training which includes the development of effective patient interactions along with understanding chronic diseases [2]. It is reported that students in family medicine (FM) conduct physical examination more frequently and gain experience in both the breadth and depth of primary care (PC) [3].…”
Section: Introductionmentioning
confidence: 99%